Analisis Determinan Pengeluaran Kesehatan Rumah Tangga Perokok di Sumatera Barat - Rezky Pradana; Melti Roza Adry (Jurnal Kajian Ekonomi dan Pembangunan, 2021)
This study aims to determine the effect of smoking behavior as measured by the tendency to smoke or not, gender, age and education on health expenditures in West Sumatra. In this study, the data used was the West Sumatra Susenas Data in 2020. The data was obtained from the Central Statistics Agency of West Sumatra. The analytical method used is Tobit Regression which is processed using the Stata program. The results of hypothesis testing found that the ratio of smokers had a negative and significant effect on health expenditure per capita in West Sumatra. Testing the second hypothesis found that gender had no significant effect on the per capita health of the people in West Sumatra. Testing the third hypothesis found that age has a positive effect on health expenditure per capita in West Sumatra while education also has a positive and significant effect on health expenditure per capita in West Sumatra.